Digging Through Space: Archaeology in the Star Wars Franchise - (:unkn) unknown (My University, 2021)
Archaeology is a slippery topic when it comes to its public presentation in various media, especially in fictional representations in books, film, TV, and video games. Archaeologists have historically been at odds with some of these productions, and various articles have analyzed these representations before. This article analyzes archaeological representations within the genre of speculative fiction, which includes the subgenera of fantasy, science fiction, and horror. One particular case study, Star Wars, will be examined in depth to see how this representation could be perceived and what that means for archaeologists. There have been various references to archaeology within Star Wars throughout its history, both before and after the Disney purchase, and all references that could be examined were. First, there is an examination of the archaeologist, and what stereotypes are present in characters recognized and named as such within the franchise. Second, the analysis turns to archaeology itself and what positive and negative factors can be drawn from the representations that are present. Last, this article will look more broadly at archaeological problems such as colonial and imperial ideals within the franchise.
Keywords: Archaeology; fiction; Star Wars; representation; colonialism